Integrative Oncology at the Clinicist's Look Chronology for the Formation and Progress of the IPT & BMP Method for Treatment of Oncological Diseases - Damyanov, Christo; Maslev, Ivan; Pavlov, Vladimir; Todorov, Alexander (Highlights on Medicine and Medical Research Vol. 10, 2021)
The current presentation displays chronologically our summarized and updated results of more than 12 years of the accumulated experience of integrative oncology application in our medical practice. Based on our concept of systemic approach, we have created treatment protocol for cancer patients with leading method of administering Insulin Potentiation Therapy (IPT). For the past 12 years period we treated more than 1100 cancer patients, greater part of which (94%) were patients with advanced metastatic tumors (?2-?4) and more than 80% of them experienced failure of previous conventional treatment for cancer with chemo- and radiotherapy. The achieved treatment results demonstrated remission in about 80% of the patients, and were presented in our earlier publications. In search for new opportunities of improvement of our treatment efficiency since April 2018, we created treatment method which includes combination of IPT with Biomagnetic therapy with magnetic pairs. (IPT & BMP). Until August 2019 this specific treatment has been applied to 33 cancer patients with advanced metastatic tumors (?2-?4) in which 19 out of 23 (82%) experienced failure of previous standard treatment. Twenty-three patients have completed their treatment and were followed up by us. Out of them, 5 patients (21%) have achieved complete remission, and 17 patients (74%) have achieved stabilization. The average remission period is 10 months up till now. Registered failed treatment is present in only one case. Illustrating the opportunities of the new method, we present herewith two new cases with the results of complete clinical remission. In our opinion, the results are an illustration of the opportunities of the Integrative oncology, and the need for change in the concept for cancer patients’ treatment. The first successful results of the treatment with combined IPT & BMP method open new therapeutic possibilities. Our achieved results give us firm ground for developing our activities in optimization of our medical practice and methodology.